Integrating Gender into Transport Planning From One to Many Tracks - Scholten, Christina Lindkvist; Joelsson, Tanja; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This edited collection brings together feminist research on transport and planning from different epistemologies, with the intention to contribute to a more holistic transport planning practice. With a feminist perspective on transport policy and planning, the volume insists on the political character of transport planning and policy, and challenges gender-blindness in a policy area that impacts the everyday lives of women, men, girls, and boys. The chapters discuss everyday mobility as an embodied and situated activity in both conceptual and theoretical ways and suggest practical tools for change. The contributions of this collection are threefold: integrating gender research and transport planning, combining quantitative and qualitative gender research perspectives and methods, and highlighting the need to acknowledge the politicization of transport planning and transport practice.
1. The political in transport and mobility - toward a feminist analysis of everyday mobility and transport planning, Tanja Joelsson and Christina Lindkvist Scholten -- 2. Are we still not there yet? Moving further along the gender highway, Clara Greed -- 3. Travel choice reframed: "deep distribution" and gender in urban transport -- 4. Gendered perspectives on Swedish transport policy-making - an issue for gendered sustainability too, Lena Smidfelt Rosqvist -- 5. How to apply Gender Equality Goals in transport and infrastructure planning, Lena Levin and Charlotta Faith-Ell -- 6. Til Work Do Us Part: The Social Fallacy of Long-distance Commuting, Erika Sandow -- 7. Measuring mobilities of care, a challenge for transportation agendas, Inés Sánchez de Madariaga and Elena Zucchini -- 8. The 'I' in sustainable planning - constructions of users within municipal planning for sustainable mobility, Malin Henriksson -- 9. Towards an intersectional approach to men, masculinities and (un)sustainable mobility: the case of cycling and modal conflicts, Dag Balkmar -- 10. Hypermobile, sustainable or safe? Imagined childhoods in the neo-liberal transport system, Tanja Joelsson -- 11. Gendering mobilities and (in)equalities in post socialist China, Hilda Roemer Christensen -- 12. Towards a feminist transport and mobility future - from one to many tracks, Tanja Joelsson and Christina Lindkvist Scholten.
Keywords: Human geography; Transportation engineering; Traffic engineering; Sex; Sociology, Urban; Human Geography; Transportation Technology and Traffic Engineering; Gender Studies; Urban Sociology